2016
DOI: 10.1093/rheumatology/kew247
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence to disease modifying antirheumatic drugs in the first year after diagnosis: comparing three adherence measures in early arthritis patients

Abstract: Associations between the three measures are weak. Explanations are individual differences in the uptake of MTX, and little variance in adherence between patients. Moreover, the measurement domains differ: perceptions (CQR), behaviour (MEMS) and pharmacokinetics (MTX).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Similar to this current study, several other studies have also used the CQR for assessing adherence in people with RA. A study in Spain with the sample size of 234 patients found 79.1% of patients as adherent; a study in Belgium found 85.7% were adherent (n = 129) and a study in Netherlands found adherence of 70%, 60.9%, 55.2% and 59.2% after 3, 6, 9 and 12 months from diagnosis (n = 170, 156, 143, 142) . The findings from this study and previous studies suggest that medication adherence in people with RA is higher in European countries than Middle Eastern countries.…”
Section: Discussionsupporting
confidence: 46%
“…Similar to this current study, several other studies have also used the CQR for assessing adherence in people with RA. A study in Spain with the sample size of 234 patients found 79.1% of patients as adherent; a study in Belgium found 85.7% were adherent (n = 129) and a study in Netherlands found adherence of 70%, 60.9%, 55.2% and 59.2% after 3, 6, 9 and 12 months from diagnosis (n = 170, 156, 143, 142) . The findings from this study and previous studies suggest that medication adherence in people with RA is higher in European countries than Middle Eastern countries.…”
Section: Discussionsupporting
confidence: 46%
“…The relationship between MMAS-8 and MPR was evaluated using Pearson’s correlation. We expected the correlation between MMAS-8 and MPR to be weak to moderate as shown in previous studies in other therapeutic areas 2022…”
Section: Methodsmentioning
confidence: 68%
“…There are a number of different methods which have been developed to measure MTX and its metabolites including assays that can detect MTX polyglutamate (MTXPG). However, in a recent study by Pasma et al, no correlation of measurement of MTXPG was found with a Medication Event Monitoring System that registers openings of the medication package; the findings did not, therefore, support the measurement of MTXPG as a biomarker of adherence 21. One possible explanation is the long t 1/2 of MTXPG; the time when MTXPG levels become undetectable, can range from 2 to 32 weeks 22…”
Section: Discussionmentioning
confidence: 89%